Investigating Knowledge of Antibiotics, Antimicrobial Resistance and Antimicrobial Stewardship Concepts Among Final Year Undergraduate Pharmacy Students in Northern Nigeria - Abdu-Aguye SN; Barde KG; Yusuf H; Lawal BK; Shehu A; Mohammed E (Dove Medical Press, 2022)
Samirah N Abdu-Aguye,1,* Kromdi G Barde,1,* Hadiza Yusuf,2,* Basira Kankia Lawal,3,* Aishatu Shehu,4,* Elijah Mohammed5,* 1Department of Clinical Pharmacy & Pharmacy Practice, Ahmadu Bello University, Zaria, Nigeria; 2Department of Clinical Pharmacy & Pharmacy Administration, University of Maiduguri, Maiduguri, Nigeria; 3Department of Clinical Pharmacy & Pharmacy Management, Kaduna State University, Kaduna, Nigeria; 4Department of Pharmacology & Therapeutics, Ahmadu Bello University, Zaria, Nigeria; 5Pharmacists Council of Nigeria, Abuja, Nigeria*These authors contributed equally to this workCorrespondence: Samirah N Abdu-Aguye, Department of Clinical Pharmacy & Pharmacy Practice, Faculty of Pharmaceutical Sciences, Ahmadu Bello University, Zaria, Nigeria, Tel +234 803 201 9135, Email sn.abduaguye@gmail.comIntroduction: Well trained, knowledgeable and competent pharmacists are indispensable in the fight against antimicrobial resistance (AMR), which is a current global public health problem. The aim of this work was to assess knowledge of antibiotics, antimicrobial resistance and antimicrobial stewardship of fifth year pharmacy students at three universities in Northern Nigeria.Methods: A descriptive cross-sectional study that used a paper-based questionnaire to collect data from July to September 2021 was conducted. The questionnaire was self-administered and divided into four sections. The first section collected information about the demographic data of respondents, while section B explored their knowledge of antibiotics and AMR. Section C contained six questions assessing knowledge of various aspects of antimicrobial stewardship (AMS), while the final part assessed respondents' preparedness to work with antibiotics and perceptions of their current knowledge of these concepts. Descriptive statistics were used to report the results obtained.Results: A total of 164 questionnaires were retrieved. Majority of respondents were male (58.3%) and aged between 21 and 25 years (53.4%). Most of them had some knowledge of antibiotics and AMR, however several misconceptions with respect to these concepts were identified. Only 80 (48.8%) of respondents indicated that they knew what AMS was, although most of these students were correctly knowledgeable about the goals and scope of AMS and composition of the AMS team. Generally, less than half of respondents agreed that their current knowledge of antibiotics, AMR or AMS was adequate for their future careers, and over 90% of them agreed that they would like more education about these topics.Conclusion: Many of the study's' respondents were somewhat knowledgeable about these concepts, although several knowledge gaps were also observed. Improving undergraduate pharmacy education with respect to these concepts is recommended.Keywords: antibacterial agents, antibiotic resistance, antimicrobial stewardship, Nigeria, pharmacy students